Evaluasi Pelaksanaan Program Rehabilitasi Sosial Rumah Tidak Layak Huni (RS-RTLH) sebagai Upaya Pengentasan Kemiskinan di Kecamatan Cibeber, Kota Cilegon - Fikri Rohmaturizky; Rahmawati Rahmawati (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) is a policy of the Cilegon Government at improving the welfare of low-income communities through housing rehabilitation, particularly in Cibeber District, where many houses are still uninhabitable. This study aims to evaluate the implementation of the program using Daniel Stufflebeam’s CIPP model (Context, Input, Process, Product). The research employed a qualitative method with a descriptive design, collecting data through interviews, observations, and documentation. The research informants consisted of the Head of the Social Protection and Security Division, the Head of the Community Empowerment for Social Welfare Section, the Social Counselor (Cilegon City Social Service), the Operational Service Officer (Cilegon City Housing and Settlement Agency), the Housing Survey Officer (Cilegon City Housing and Settlement Agency), and the Head of Neighborhood Association (RW 02) of Link Kerotek, Kalitimbang Subdistrict, Cibeber District. The results show that the 2023 program did not run well. Many people still need proper housing. The budget was too small, so many proposals were not accepted, and the help given was not enough to fix the houses completely. During the process, the coordination between the related offices was not good, and there were also problems with bureaucracy and the e-grant system. The program was helpful for some people, but it did not really improve the overall housing condition. Overall, the RS-RTLH program has given some support to the community, but it still needs better budget management, clear information, and good cooperation between offices to work more effectively and reach more people.